Chicken breast muscle hydrolysates ameliorate acute alcohol-induced liver injury in mice through alcohol dehydrogenase (ADH) activation and oxidative stress reduction. Issue 2 (8th January 2018) - Xiao, Chuqiao; Zhou, Feibai; Zhao, Mouming; Su, Guowan; Sun, Baoguo
Abstract : In this study, the ameliorative effect of chicken breast muscle hydrolysates (CBMHs) against acute alcohol-induced liver injury was investigated and its probable mechanism was further elucidated. Abstract : In this study, the ameliorative effect of chicken breast muscle hydrolysates (CBMHs) against acute alcohol-induced liver injury was investigated and its probable mechanism was further elucidated. In vitro studies clearly showed that CBMHs are able to activate alcohol metabolic enzymes ( i.e. alcohol dehydrogenase, ADH) in an exponential manner. Meanwhile, an in vivo experiment on male NIH mice indicated that the oral administration of CBMHs (150, 300 and 600 mg per kg bw) 30 min prior to acute alcohol ingestion could significantly promote alcohol metabolism as revealed by the reduced duration of the loss of righting reflex (LORR) and the enhanced activity of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) in the liver, the latter accelerating alcohol oxidation and therefore the decreased blood alcohol concentration (BAC) level. Pretreatment with CBMHs significantly decreased the elevations of serum aspartate transaminase (AST) and alanine transaminase (ALT) after alcohol administration. CBMHs could also retard lipid peroxidation as revealed by the suppressed malondialdehyde (MDA) level and simultaneously enhance the activities of superoxide dismutase (SOD) in liver tissue. Furthermore, increased histological damage and higher ( p < 0.05) hepatic triglyceride (TG) contents in acute alcoholic-diet fed mice were also reduced ( p < 0.05) by supplementing with CBMHs. These benefits clearly suggested that CBMHs could be a potential nutraceutical to facilitate alcohol metabolism and prevent or ameliorate early liver injury induced by acute alcohol exposure.